Researching in the age of Covid-19: Volume III: Creativity and ethics - Kara, Helen; Khoo, Su-Ming (Bristol, UK : Policy Press, an imprint of Bristol University Press, 2020)
"As researchers continue to adapt, conduct and design their research in the presence of COVID-19, new opportunities to connect research creativity and ethics have opened up. Researchers around the world have responded in diverse, thoughtful and creative ways -adapting data collection methods, fostering researcher and community resilience, and exploring creative research methods. This book, part of a series of three Rapid Responses, explores dimensions of creativity and ethics, highlighting their connectedness. It has three parts: the first covers creative approaches to researching. The second considers concerns around research ethics and ethics more generally, and the final part addresses different ways of approaching creativity and ethics through collaboration and co-creation. The other two books focus on Response and Reassessment, and Care and Resilience. Together they help academic, applied and practitioner-researchers worldwide adapt to the new challenges COVID-19 brings"--Publisher's description
Part I. Creative approaches -- The creative translation of design methods into social research contexts -- 'Crafting during Coronavirus': Creative diary approaches for participant-centred research -- Decolonizing writing: Situating insider-outsider researchers in writing about COVID-19 -- Pandemic tales: Using story completion to explore sense-making around COVID-lockdown restrictions -- Part II. Exploring ethics. Conceptualizing research ethics in response to COVID-Moral and economic contradictions -- COVID-research crisis management for a human research ethics research project in Fiji and Tonga -- Forced displacement of migrants from countries of origin and their transit migration through Mexico to the US -- Transforming culturally relevant research amid a COVID-pandemic -- Part III. Approaching creativity and ethics through collaboration and co-creation. Using photovoice to explore students' study practices -- Scicurious as method: Learning from GLAM young people living in a pandemic about cultivating digital co-research-creation spaces that ignite curiosity and creativity -- Doing design research with youth at/from the margins in pandemic times: Challenges, inequalities and possibilities -- Conclusion.
Includes bibliographical references and index.
Online resource; title from resource home page (JSTOR, viewed October 18, 2021).
JSTOR
Keywords: Social sciences -- Research; COVID-19 (Disease) -- Research; Creative ability; COVID-19 -- psychology; Social Sciences -- methods; Ethics, Research; Research Design; Creativity; Sciences sociales -- Recherche; COVID-19 -- Recherche; Créativité.; creativity; SOCIAL SCIENCE / Methodology; Creative ability; COVID-19 (Disease) -- Research; Social sciences -- Research